The cost of elective nodal coverage in prostate cancer: Late quality of life outcomes and dosimetric analysis with 0, 45 or 54 Gy to the pelvis. (September 2022) - Jensen, Garrett L.; Jhavar, Sameer G.; Ha, Chul S; Hammonds, Kendall P.; Swanson, Gregory P.
Highlights: Pelvic nodal radiation to 54 Gy correlates with worse urinary quality of life. Pelvic nodal radiation to 45 Gy does not correlate with urinary quality of life. Post-operative radiation resulted in greater urinary quality of life decline. Pelvic nodal radiation did not correlate with bowel quality of life. Abstract: Purpose: Elective pelvic lymph node radiotherapy (PLNRT) in prostate cancer is often omitted from definitive (n = 267) and post prostatectomy (n = 160) radiotherapy (RT) due to concerns regarding toxicity and efficacy. Data comparing patient-reported outcome measures (PROMs) with or without PLNRT is limited. Our long-term supposition is that PLNRT, particularly to higher doses afforded by IMRT, will decrease pelvic failure rate in select patients. We aim to establish the impact of two different PLNRT doses on long term quality of life (QOL). Methods and materials: Prostate cancer patients (n = 428) recorded baseline scores using the Expanded Prostate Cancer Index Composite (EPIC), prior to definitive or post-prostatectomy RT. PLNRT, if given, was prescribed to 45 or 54 Gy at 1.8 Gy per fraction. New EPIC scores were recorded 20–36 months after radiotherapy. Absolute change in each domain subscale and summary score was recorded, along with if these changes met minimally important difference (MID) criteria. A separate multivariate analysis (MVA) was performed for each measure. Subsequent dosimetric analysis was performed. Results: Frequency of a MID decline was significantly greater with PLNRT to 54 Gy for urinary function, incontinence, and overall. No urinary decline was correlated with PLNRT to 45 Gy. PLNRT to 54 Gy was significant for decline in urinary function, bother, irritative, incontinence, and overall score in one or both MVA models while 45 Gy was not. Postoperative status was significant for decline in urinary function, incontinence, and overall. Amongst postoperative patients, there was significantly greater decline in urinary function score in the salvage setting. Neither 54 nor 45 Gy significantly affected bowel subscale or overall score decline. Conclusions: Using conventional fractionation, adding PLNRT to 54 Gy, but not 45 Gy, correlates with worse urinary QOL, with postoperative patients experiencing a steeper decline. PLNRT had no significant impact on bowel QOL with either dose.